2009
DOI: 10.1007/s11105-009-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

MaSERK1 Gene Expression Associated with Somatic Embryogenic Competence and Disease Resistance Response in Banana (Musa spp.)

Abstract: A banana somatic embryogenesis receptor-like kinase (SERK) gene, designated as MaSERK1, was isolated from Musa acuminata cv. Mas (AA). It encoded a protein of 628 amino acids with above 82% identities to reported SERKs of coconut, rice, maize, Arabidopsis, carrot, and Medicago truncatula. MaSERK1 was expressed weakly in male flower clusters, but not in male flower-derived nonembryogenic calli, but it was highly expressed in male flower-derived embryogenic calli and embryogenic cell suspensions (ECS). During su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…The expression analysis of AcSERK1 in the nonembryogenic callus and organs, such as leaf, stem, and calyx, showed that AcSERK1 expression occurred at lower levels than those observed in embryogenic tissues, thus suggesting that AcSERK1 is associated with SE induction in pineapple, but it belongs to non-featured expression in embryogenic callus. This result was different with those obtained from carrot (Schmidt et al 1997), Arabidopsis , and banana (Huang et al 2010), where SERK was only expressed in embryogenic callus. However, the high expression level of AcSERK1 during the acquisition of embryogenic competence and the development of global embryo is similar to the SERKs above.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The expression analysis of AcSERK1 in the nonembryogenic callus and organs, such as leaf, stem, and calyx, showed that AcSERK1 expression occurred at lower levels than those observed in embryogenic tissues, thus suggesting that AcSERK1 is associated with SE induction in pineapple, but it belongs to non-featured expression in embryogenic callus. This result was different with those obtained from carrot (Schmidt et al 1997), Arabidopsis , and banana (Huang et al 2010), where SERK was only expressed in embryogenic callus. However, the high expression level of AcSERK1 during the acquisition of embryogenic competence and the development of global embryo is similar to the SERKs above.…”
Section: Discussioncontrasting
confidence: 91%
“…These results indicated that SERK plays an important role in SE, and it can be used as a marker of embryogenic competence. Dissimilar expression patterns were found in soybean and banana (Huang et al 2010;Yang et al 2011). It suggested that SERK may be involved in plant development, disease resistance, or other procedures (Alam et al 2010;Huang et al 2010;Yang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous research that demonstrated that OsSERK1 showed variable expression levels in different tissues, as well as by the host defense against fungal infection and positively regulated somatic embryogenesis of cultured cells (Hu et al, 2005). Moreover, MaSERK1 was found to be associated with disease resistance response and somatic embryogenic competence (Huang et al, 2010). However, further analysis of the functions of MhSERK1 and MhdSERK1 in different organs and tissues is required.…”
Section: Discussionsupporting
confidence: 91%
“…OsSERK1 is thought to be partially responsible for mediating defense signal transduction and has a basic role in rice somatic embryogenesis (Hu et al, 2005). More homologs of SERK have been identified in several plant species, including Dactylis glomerata (Somleva et al, 2000), Medicago truncatula (Nolan et al, 2003(Nolan et al, , 2009, Ocotea catharinensis (Santa-Catarina et al, 2004), Helianthus annuus (Thomas et al, 2004), Theobroma cacao (Santos et al, 2005), Citrus unshiu (Shimada et al, 2005), Triticum aestivum (Singla et al, 2008), Vitis vinifera (Schellenbaum et al, 2008), Solanum tuberosum (Sharma et al, 2008), Cocos nucifera (Perez-Núñez et al, 2009), Lactuca sativa (Santos et al, 2009), Rosa hybrida (Zakizadeh et al, 2010), Musa acuminata (Huang et al, 2010), Secale cereale (GruszczyĹ„ska and Rakoczy-Trojanowska, 2011), Glycine max (Yang et al, 2011), Cyclamen persicum (Savona et al, 2012), Ananas comosus (Ma et al, 2012a,b), and Cyrtochilum loxense (Cueva et al, 2012). These reports all point to SERK as a specific marker of embryogenic competence during morphogenesis induction.…”
Section: Introductionmentioning
confidence: 99%